2012
DOI: 10.1007/s00128-012-0794-5
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of Heavy Metals in Groundwater in Chennai City Using a HPI Model

Abstract: Heavy metal contamination in Chennai city was evaluated using a heavy metal pollution index (HPI) model in conjunction with the spatial distribution maps. Metals such as Cd, Cr, Cu, Pb and Zn in the groundwater were determined using standard methods and the resultant data was utilized in the development of a HPI model. The metal concentrations showed a dominance in the order of Zn > Cu > Cr > Pb > Cd respectively. About 14.3 % of the samples (n = 2), exhibited high HPI (>38) and the highest value, HPI = 97.55,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(18 citation statements)
references
References 12 publications
3
12
0
1
Order By: Relevance
“…Therefore, it could also be attributed to the seepage of ESEs from the surface to the aquifer during monsoon season in the industrial areas. Similar studies from other parts of India have also reported that groundwater beneath industrial establishments is generally contaminated with heavy metals [51][52][53]. Although Fe is an essential element for human beings, a higher Fe concentration in drinking water can cause certain health impacts [54].…”
Section: Carcinogenic Risk Assessmentmentioning
confidence: 56%
“…Therefore, it could also be attributed to the seepage of ESEs from the surface to the aquifer during monsoon season in the industrial areas. Similar studies from other parts of India have also reported that groundwater beneath industrial establishments is generally contaminated with heavy metals [51][52][53]. Although Fe is an essential element for human beings, a higher Fe concentration in drinking water can cause certain health impacts [54].…”
Section: Carcinogenic Risk Assessmentmentioning
confidence: 56%
“…This is dependent on the psychochemical parameters, where the solubility of the heavy metals increased with the decrease of pH values, which clarifies that the correlation occurs between heavy metals and physicochemical parameters. Fe is highly correlated with Mn, which suggests that they might come from a common source [ 79 ]. Fe and Mn can be released from geogenic sources as they are common elements in rocks and minerals [ 80 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regular monitoring of all water resources and water points should be ensured to help determine problem regions, source of pollution and design a frame work of corrective plans. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]…”
Section: Discussionmentioning
confidence: 99%